Transition in Southeast Europe: Understanding economic development and institutional change - Milica Uvalic (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
The paper analyses the 20-year experience with transition in the SEE countries in a comparative framework, illustrating how these countries encountered difficulties in its implementation, despite having some of the best starting conditions in 1989 to implement a swift transition to a market economy. The paper recalls the initial conditions in the SEE region in 1989, macroeconomic performance and progress achieved in the various transition-related economic reforms. The international issues are also addressed related to the post-2000 integration of the SEE countries with the EU and among themselves. The paper also reflects on the main factors that are responsible for delays in transition in SEE related to political instability, delayed integration with the EU, and inappropriate economic policies.
Keywords: P20; P27; P30; P33; O10; 330; economic transition; Southeast Europe; economic development; institutional change; EU integration